Evaluating the effects of biogeography and fragmentation on the taxonomic, functional, and genetic diversity of forest-utilising bats in a South African biodiversity hotspot - Moir, Monika Ilka (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.